Implementasi Kebijakan Dinas Pendidikan Dalam Meningkatkan Profesionalisme Guru Pendidikan Agama Islam (PAI) Di Kabupaten Bojonegoro - Vira Virnanda; Sri Minarti (Badan Usaha Milik Desa Berkaho Pungpungan, 2026)
This research examines the implementation of policies carried out by the Department of Education in improving the professionalism of Islamic Religious Education (PAI) teachers in Bojonegoro Regency. PAI teachers have a strategic responsibility in developing students’ character, ethics, and religious values, making professional competence an essential requirement in responding to educational transformation and technological advancement in the contemporary era. This study applied a descriptive qualitative method with a policy analysis framework. The data were obtained through in-depth interviews with officials of the Education Department, PAI supervisors, school principals, and PAI teachers, supported by documentation studies related to educational development programs and policies. The findings demonstrate that the Department of Education of Bojonegoro Regency has introduced several strategic programs, including strengthening Teacher Working Groups (KKG) and Subject Teacher Deliberation Forums (MGMP), conducting continuous professional development training, and improving teacher distribution across educational institutions. Nevertheless, policy implementation continues to face several challenges, such as inadequate budget allocation specifically for PAI teacher development, weak coordination between the Education Department and the Ministry of Religious Affairs, and differences in digital literacy among senior teachers. Therefore, this study emphasizes the necessity of strengthening institutional cooperation and integrating technology-based professional development programs to support the equitable enhancement of PAI teacher professionalism.